The essential guide to Christianity - Daughrity, Dyron B. (The essential guides to religion, 2024)
"Chapters explore topics including the Bible, Sacraments, Women in Christianity, Catholicism, Protestantism, and the Eastern Orthodox tradition, as well as the considering the future of Christianity. The book is illustrated with over 60 images, and a glossary of key terms and concepts is provided. Each chapter offers suggestions for further reading"--